PENINGKATAN KECERDASAN EMOSIONAL (EMOTIONAL QUOTION) ANAK USIA DINI MELALUI PENDIDIKAN SENI TARI - Kusumastuti, Eny (Universitas Negeri Semarang, 2009)
Education with a dimension of EO (Emotional Quotions) can be found in theconcept of dance education. This article is the result research that examine how theimplementation process, and improvement of emotional intelligence of youngchildren through learning the art of dance by using a qualitative approach. Data iscollected through focused interviews, participant observation, and studydocumentation. The data is analyzed by reducing, clarifyng, describing, concluding,and interpreting all the information. The data is then examinated its confirmabilityand dependability. The result showed the implementation process of dance educationin early childhood dependent on its teaching and learning process, which includes:objectives, teaching material, teaching methods and learning activities, facilities andinfrastructure, evaluation, social and cultural conditions. The improvement ofemotional intelligence of young children through learning the art dance can be seenthrough: (1) a sense of pridfe, (2) has a brave nature, (3) able to control emotions, (4)able to hone refinement, (5) be able to nuture a sense of responsibility, (6) able tonuture a sense of self, (7) easy to interact with others, (8) has a good performance, (9)are able to develop imagination, and (10) becomes a creative child.Kata Kunci: pendidikan seni tari, kecerdasan emosional, dan anak usia dini